DETERMINAN MINAT MAHASISWA MENJADI GURU - Caubita Valentin; Satrijo Budiwibowo; Nur Wahyuning Sulistyowati (LP3M Universitas Muhammadiyah Muara Bungo, 2019)
The purpose of this study was to determine the interest of students to become teachers in students of Accounting Education Study Program FKIP XYZ University. This study uses quantitative methods with descriptive statistical data analysis techniques. The sampling technique uses purposive sampling. Data collection of this study using a questionnaire. The results obtained from this study are family environment, microo teaching, apprenticeship III affect the interest of students to become teachers. Can be seen by the motivation given and the economic situation in the family environment, the ability to manage the class in microo teaching, as well as teaching and non-teaching activities that exist in apprenticeship III.